The Dominance of Tramps Ants in The Settlement Area of Semarang, Central Java - Putra, Ivan Mahadika; Hadi, Mochammad; Rahadian, Rully (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2019)
The high rate of urbanization in Semarang have caused the land conversion from forest into various human need spaces. The land conversion is not only affect the life of humans but also the animals, including ants. The objectives of this study were to examine the dominance of tramp ants in the settlement area of Semarang City. The method used was the bait trap method using chicken intestine as a bait. Samples of ants were collected from four habitats, i.e., waste disposal area, traditional markets, house area, and urban parks. This study found four dominant ants, i.e., Anoplolepis gracilipes, Paratrechina longicornis, Solenopsis geminata and Monomorium pharaonis. Two of them were categorized as tramp ants (Anoplolepis gracillipes and Paratrechina longicornis). The highest diversity of ants was found in house (H'= 2.72). The waste area tends to be an ideal habitat for particular species, which was proved by the low value of Simpson's dominance index (iD = 0.06) and a high value of evenness index (E=0 0.89). This study provides new information about tramp ants population as pest in urban area. The findings would be beneficial for controlling the population of tramp ants, which are disturbing humans in the settlement area.